In Vitro Propagation of Chrysanthemum morifolium Ramat Using Stem Nodal Explants - Mohamed, Nagat Salih; Mohamed, Seifeldin Ali; Mohamed Idris, Tagelsir Ibrahim (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to investigate the effect of some growth regulators on in vitro shoot regeneration, multiplication and rooting of Chrysanthemum morifolium to develop a protocol for its mass propagation. Nodal explants of C. morifolium were cultured on MS basal medium supplemented with the cytokinins BAP and kinetin, both at 0.0, 0.1, 0.2, 0.5, 1.0, 2.0, 5.0, 10.0 mg/l, for shoot regeneration. The regenerated shoots were separated from the nodal explants and cultured on MS medium supplemented with BAP and kinetin, both at 0.0, 0.1, 0.2, 0.5 mg/l for shoot multiplication. The shoots were then cultured on MS medium supplemented with 0.0, 0.1, 0.2, 0.5 mg/l of IBA for rooting. Twenty explants were used per treatment. The percentage of responded explants, average number of shoots per explant, length of shoot, percentage of rooted shoots, number of roots per shoot and length of root were determined. The concentration of 0.1 mg/l of both BAP and kinetin showed the best response with regard to shoot regeneration and multiplication giving the highest number of shoots per explant. Cytokinin–free medium gave significantly the highest length of shoot. All IBA treatments gave 100% rooting. However, MS+ 0.5 mg/l IBA resulted in significantly the highest number of roots per shoot, and IBA–free medium resulted in significantly the highest root length